The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.5604/15093492.1097487
|View full text |Cite
|
Sign up to set email alerts
|

Results of Two-Stage Operative Treatment of Anteromedial Instability of the Knee

Abstract: 1.Two-stage operative treatment produces good or very good results in most patients. Nevertheless, there is a risk of complications in some cases, mostly in patients aged 40 years. Accordingly, two-stage treatment is currently recommended in younger individuals. 2. A complete MCL tear at the distal attachment should be given particular attention. Although such injury is rare, due to the anatomical determinants and the risk of Stener-like lesions, i.e. unhealed ML, surgery is recommended. Surgery produces good … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The same study reported a mean Lysholm score of 94.5, an ACL stability side-to-side difference of 2.3 mm and no valgus or rotational instability at follow-up. Nakamura et al [31] compared MCL reconstruction versus conservative MCL treatment in combination with ACL knee injuries and found no between-group differences in subjective or objective (valgus laxity) outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same study reported a mean Lysholm score of 94.5, an ACL stability side-to-side difference of 2.3 mm and no valgus or rotational instability at follow-up. Nakamura et al [31] compared MCL reconstruction versus conservative MCL treatment in combination with ACL knee injuries and found no between-group differences in subjective or objective (valgus laxity) outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…According to the American Medical Association classification [2], MCL injuries can be divided into three categories (grades I–III) according to the level of medial structural injury and valgus laxity. Grade III MCL injuries often present in combination with ACL tears [1, 31]. A recent epidemiological study on knee injuries among 17,397 patients with 19,530 sports‐related injuries over a 10‐year period found 7.9% of isolated MCL lesions [23].…”
Section: Introductionmentioning
confidence: 99%
“…Osteoarthritis of the knee is defined as a set of changes involving articular cartilage damage, abnormal bone formation, reactive changes in the synovial membrane, and pathologic synovial fluid [1]. It has recently become an important public health issue, the frequency of which is increasing day by day, due to the aging population all over the world as well as in Türkiye, the increased prevalence of obesity, and the rapid world population growth.…”
Section: Introductionmentioning
confidence: 99%
“…TCM recognizes that the knee joint relies on various structures, including bones, tendons, ligaments, and cartilage, to facilitate movement and support the body. [1] Wind is considered to be the cause of around a hundred diseases in TCM and can cause havoc by moving pain from joint to joint. External pathogenic factors such as cold can also enter the body and cause severe pain, especially in the knee joint.…”
Section: Introductionmentioning
confidence: 99%